Lure of dividend yields the case of 20 dividend stocks in Malaysia - Ling Leh Bin, Raymond; Peck Ling, Tee. (International Journal of Engineering and Technology, 2018)
Following the 2016 prevailing negative interest rates in some advanced economies, Malaysia high-yielding dividend stocks could emerge as a new asylum for both foreign and local investors who seeking good returns. Rationale portfolio investors enjoy returns when stocksâ€™ prices appreciate and provided dividend yields are still attractive, particularly in large-cap dividend (income) stocks. Large-cap dividend stocks would get rerated as efficient and optimal portfolio as more foreign funds flow into them. Conversely, small-to mid-cap dividend stocks below RM1 billion market capitalization are also worth investing. When the market moves, smaller cap companies will obtain a higher leverage in the light of price movement. By investigating the 20 Malaysian dividend stocks that would sustain the risk adjusted performance measure, these portfolio will be compared, analysed and ranked relatively by utilizing the correlation-covariance methodology and the Sharpe Index. The REITs are able to provide higher cash dividend pay-outs and favoured an optimal portfolio selection. Given a greater local market exposure, fuelled by domestic demographics and rising middle class, small-cap dividend stocks will still be new safe havens to both local and foreign institutional funds.Â